Second order differential equation - Mahat, Aishah; Irdina, Nur Hasya; Waheeda, Nafisa (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This eBook was created to offer a clear, intuitive, and structured introduction to the core concepts of calculus: limits, derivatives, integrals, and their applications. Whether you're a student encountering calculus for the first time, a self-learner brushing up on fundamentals, or an instructor seeking a supplemental resource, this book is designed to guide you step-by-step through the subject with clarity and purpose. Our goal is not only to help you succeed in calculus but to foster an appreciation for its power, elegance, and relevance.